Finger Millet Consumption: A study on Knowledge, Attitude and Practices in North Coastal Region of Andhra Pradesh - Anusha, Beera; Naik, Akkamahadevi; Kumar, Ashok; Reddy, Idemakanti Chandrakanth (Indian Journal of Extension Education, 2024)
Finger millet (Eleusine coracana L.), commonly known as Ragi or Mandia, holds significant importance in global agriculture due to its nutritional richness, adaptability, and its potential to address food security challenges. It serves as a vital crop contributing to sustainable food systems and nutrition security worldwide. The study was conducted from 2023 to 2024, gathering data from 120 consumers across three districts in the North Coastal Region of Andhra Pradesh, namely Srikakulam, Vizianagaram, and Visakhapatnam through personal interview method and revealed that the majority of consumers were aged 36-50 years, mostly male, and educated up to graduation level. Business activities were predominant in Srikakulam (40%) and Vizianagaram (50%), while Visakhapatnam had a higher proportion of government employees (30%). Household incomes varied, with Srikakulam and Vizanagaram ranging from 50,000 to 1,00,000 rupees, and Visakhapatnam from 1,00,000 to 2,00,000 rupees. Finger millet malt was favored across dishes in all districts, but consumption frequency differed. In Srikakulam (41.40%) and Vizianagaram (35%), consumption was less frequent, while in Visakhapatnam, 29% consumed it weekly or monthly. Reasons for consumption also varied, with health benefits cited in Srikakulam (41.40%), weight management in Vizianagaram (29%) and Visakhapatnam (36%).
Keywords: Finger millet; Consumer; Attitude; Practice